Pemeranan Tokoh Pelayan I Dalam Naskah Ba-Bi & Ba-Bu Karya Jean Genet Menggunakan Metode Stanislavski - Saputri, Windi Dwi; Soeryana, Dharminta; Susanti, Desi (Laga-Laga : Jurnal Seni Pertunjukan, 2025)
Servant I is a character in the Ba-Bi & Ba-Bu script by Jean Genet translated by Asrul Sani Adapted by Rachman Sabur which was the choice of the Final Exam for the interest in Acting by the author. This script is an absurdist script that can be seen from Martin Jullius Esslin in his book The Theatre Of The Absurd discussing Jean Genet. Jean Genet himself was one of the pioneers of absurd theater that greatly shook the world's thinking at that time. The Ba-Bi & Ba-Bu script is a representation of life between the master and his two servants. Servant one is an association of an unstable psyche that occurs due to pressure from the environment. The actor plays the role of the Grand Lady for substitutive satisfaction of her compulsive obsession with fate, but in the end she is suffocated in her own game. Servant I represents the prisoner's daydream, the fantasy of an outcast who makes a futile effort to teach the world about acceptance and ownership. The process of developing and identifying the character of this servant one uses the reference book "Becoming an Actor" by Suyatna Anirun with an effort to apply the Stanislavsky Method described.